2015
DOI: 10.1007/s12194-015-0321-6
|View full text |Cite
|
Sign up to set email alerts
|

Signal-to-noise ratio and parallel imaging performance of commercially available phased array coils in 3.0 T brain magnetic resonance imaging

Abstract: The signal-to-noise ratio (SNR) and parallel imaging (PI) performance of two commercial phased-array coils (PACs) were examined in magnetic resonance imaging (MRI) of the brain. All measurements were performed on a 3.0 T MRI instrument. The SNR and PI performance were evaluated with 32-channel and 15-channel PACs. A gradient echo sequence was used for obtaining images of a phantom. SNR and geometry factor (g-factor) maps were calculated from two images with identical parameters. Horizontal and vertical profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In particular, a CS AF of 4 demonstrated similar SNRs to a SENSE AF of 2, with a reduction in scan time of 40 %. Previous reports showed that higher AFs not only increased noise amplification or the average g factor, but also had a considerable negative influence on the SNR [14,19]. These previous results were similar to our findings showing that the SNR decreased as the AF increased, with either CS or SENSE.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, a CS AF of 4 demonstrated similar SNRs to a SENSE AF of 2, with a reduction in scan time of 40 %. Previous reports showed that higher AFs not only increased noise amplification or the average g factor, but also had a considerable negative influence on the SNR [14,19]. These previous results were similar to our findings showing that the SNR decreased as the AF increased, with either CS or SENSE.…”
Section: Discussionsupporting
confidence: 92%
“…19 A previous study demonstrated rapid increases in the average g factors obtained with a 32-channel phased-array coil as AF increased. 20 Therefore, these results suggest that the increase in coil g factors has much influence on the SNR as the shorter TE value.…”
Section: Discussionmentioning
confidence: 79%
“…131,132 The SNR is routinely evaluated in MRI by measuring the signal intensity difference between the region of interest (ROI) and the background. 133…”
Section: Fmrs Protocolmentioning
confidence: 99%
“…131,132 The SNR is routinely evaluated in MRI by measuring the signal intensity difference between the region of interest (ROI) and the background. 133 When MRI is used instead of 2D imaging, volume acquisition can increase the SNR. However, imaging time for spin-echo sequences is longer than GRE sequences.…”
Section: Advanced Mr Techniquesmentioning
confidence: 99%